Impact of total quality management practices on innovation in service organizations - Ahmed Mustafa, Esam Mohamed (2015)
During the last two decades, service industries have contributed significantly to the increase of Gross Domestic Products nationally and globally in developed and developing economies. Innovation has significant role in adding the competitive advantage in the scenario. Innovation in service organizations has become an important subject in both theoretical and practical research agenda. The important of service innovation is delineated from the importance of service in manufacturing organizations. It has been proven that implementing Total Quality Management (TQM) system enhances innovation and its process through its practices. Many studies have investigated the relationship between TQM and innovation and mostly not in service organizations context. This study investigates the impact of TQM on innovation in service organizations. Most of those studies did not focus on the relationship between TQM and innovation in services organizations. In addition, most of those studies did not recommend specific TQM practices that may influence innovation more than the other practices. This study aimed to examine the impact of TQM practices on innovation and identify which practices may have more influence on innovation then to come out with a model to be recommended in this relationship. Data were collected using survey method from service organizations which operate in Malaysia under different service subsectors. Confirmatory Factor Analysis technique was used to validate the constructs included in the research model. The measurement model was validated using Goodness of Fit indices, Standardized regression Weight, Convergent validity, Content validity, Discriminant validity and Multicoleanarity assessment. Structural Equation Modeling using Analysis of Moment Structures software AMOS was used to test the hypotheses. Hypotheses testing revealed that practices of customer focus and people management are the highest TQM practices that positively impact innovation in the surveyed vi organizations. It also appeared that Radical Process Innovation and Radical Service Innovation are the most innovation types that positively influenced by TQM practices. This study has contributed with novel results characterized by unique TQM practices in service organizations. This study has come out with a model on the impact of TQM practices on innovation in service. The study has added the perspective of service organizations to the debate on the relationship between TQM and innovation. Results of this study are applicable in both private and public service organizations. Managers and practitioners in service organizations can use this study to employ TQM for innovation.